The Employment of Touch in Christopher Marlowe’s Edward II - Jason O'Toole (Journal of Marlowe Studies)
Christopher Marlowe’s Edward II demonstrates the power embodied in the sense of touch as it breaks down and reveals the transitory nature of socially-constructed boundaries such as formal behaviour, contemporary terms of sexuality, and social class. While Marlowe employs metaphor to convey the sense, his engagement remains strikingly literal. This article begins by providing a brief overview of the queer, historical, and political critical analysis of Christopher Marlowe’s Edward II (1594). I investigate how Marlowe details moments of male-male affective intimacy between King Edward II and his favourite, Gaveston, through physical contact which breaks with formality and which merges the men together into a composite body or complete “self”. As tension arises between the body natural and the body politic, precious objects such as the miniature temporarily substitute tactile pleasures between the men. I continue by exploring how touching and being touched between the king and his favourite vie with and surpass intimacy between the king and queen and how it additionally extends beyond desire into a demonstration of power. Negotiations are made, accepted, and rejected through corporeal contact and public displays of affection define and signal markers of social status. I then move on to establish that while private moments of intimacy between men remain unproblematic, they are shaped not only by those who create them but by those who interpret them. The elite perceive ambition of the lower-class favourite rather than desire as the driving influence behind sexual touch and their fear lies in the wider implications of a redistribution of power and of the contamination of the social classes. This essay therefore aims to demonstrate how Marlowe understands touch not as a base sense, but as a complex primal force which moves outwards from the habitual and interweaves the sexual, social, and political.